2020
DOI: 10.15252/embj.2020106123
|View full text |Cite
|
Sign up to set email alerts
|

Cell softness regulates tumorigenicity and stemness of cancer cells

Abstract: Identifying and sorting highly tumorigenic and metastatic tumor cells from a heterogeneous cell population is a daunting challenge. Here, we show that microfluidic devices can be used to sort marker‐based heterogeneous cancer stem cells (CSC) into mechanically stiff and soft subpopulations. The isolated soft tumor cells (< 400 Pa) but not the stiff ones (> 700 Pa) can form a tumor in immunocompetent mice with 100 cells per inoculation. Notably, only the soft, but not the stiff cells, isolated from CD133+, ALDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 60 publications
0
93
0
Order By: Relevance
“…Previous studies on cancer cells have shown a strong correlation between malignancy and the mechanical properties of cells [10][11][12]42,45,49 . Here, we exploit this correlation for detecting malignancy in human tissue biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on cancer cells have shown a strong correlation between malignancy and the mechanical properties of cells [10][11][12]42,45,49 . Here, we exploit this correlation for detecting malignancy in human tissue biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found differences between the mechanical properties of cancer cells and their healthy counterparts 11,12,[42][43][44][45] . A major drawback of these studies is laborious sample preparation and low throughput that limits the conversion of these studies to actual diagnostic approaches.…”
Section: The Physical Phenotype Of Cells Is Distinct In Tumour Versus Healthy Mouse Colon Tissuementioning
confidence: 95%
“…An ex vivo analysis of cells from metastatic cancer patient samples using AFM also shows a low stiffness profile (Cross, Jin, Rao, & Gimzewski, 2007 ). A recent report that utilizes the softness trait to separate soft tumor cells from stiff tumor cell population using a microfluidic‐based method reveals that these soft cells are much more tumorigenic and metastatic than stiff tumor cells (Lv et al, 2020 ), suggesting that the cell softness is a physical marker for malignant solid tumors (Figure 2 ), adding a new physical trait to the known four physical traits (tumor tissue solid stress, interstitial fluid pressure, tumor tissue stiffness, and tumor microarchitecture) of solid tumors that may hamper successful treatment of malignant tumors (Nia, Munn, & Jain, 2020 ). The stiffness of these malignant soft tumor cells in suspension is only one‐third of the stiffness of those differentiated tumor cells (Lv et al, 2020 ), suggesting that their intrinsic cytoskeletal prestress is much lower than that in those stiff tumor cells.…”
Section: Low Prestress In Soft Stem Cell‐like Tumor Cells Promotes Tumorigenicity and Metastasismentioning
confidence: 99%
“…Based on such biomechanical understanding, a tumor cell‐derived, drug‐loaded MP treatment platform has been developed. Highly tumorigenic tumor‐repopulating cells are very soft (Lv et al, 2020 ) and preferable to take up drug‐packing MPs via their high deformability. In turn, MPs mobilize the endo‐lysosomal systems, allowing the drug molecules to be delivered to the nucleus, thus killing tumor‐repopulating cells and reversing their drug resistance (Jin et al, 2017 ; Ma et al, 2016 ).…”
Section: Extracellular Vesicles and Prestressmentioning
confidence: 99%
“…Knockdown of TAB2 in Siha and MS751 cells significantly downregulated sphere-forming efficiency (Figures 4(c) – 4(e) ). Furthermore, aldehyde dehydrogenase (ALDH) activity, a reliable marker for CSCs, mediated by TAB2 in CC cells was determined [ 14 , 15 ]. The ALDH activity was significantly reduced in CC cells transfected with si-TAB2 compared with that of negative controls (Figures 4(f) and 4(g) ).…”
Section: Resultsmentioning
confidence: 99%